Chapter On the Optical Response of Nanoparticles: Directionality Effects and Optical Forces - Garcia-Camara, Braulio; Gonzalez, Francisco; Moreno, Fernando; Gomez-Medina, Raquel; Saenz, Juan Jose; Nieto-Vesperinas, Manuel (InTechOpen, 2012)
Organic chemistry
English
Keywords: Polymer chemistry; Mathematics & science